Interpersonal Communication between Husband and Wife Suffering from Polycystic Ovary Syndrome in the City of Surabaya - Ernasari, Lidya; ., Sumardjijati (Jurnal Dakwah dan Komunikasi, 2023)
Reproductive health problems, namely PCOS (Polycystic Ovary Syndrome) experienced by married couples in Surabaya, affect the interpersonal communication that occurs between partners, difficulties in conceiving children and the risk factors that are brought about, which further worsen the condition of the relationship if the couple is not open and supportive to each other. This study aims to analyze interpersonal communication that occurs between husband and wife with PCOS and determine the obstacles experienced while undergoing treatment. This research was conducted using a qualitative descriptive method with data collection techniques from interviews and documentation studies. The results of the research show that communication between husband and wife with PCOS sufferers in Surabaya is well established with openness to be honest about their condition with their partner, empathy shown both through words and behavior, a mutually supportive attitude when facing PCOS challenges, a positive attitude and equality in accept the fact. The obstacles experienced by PCOS husband and wife couples are process obstacles due to busy schedules disrupting the regularity of treatment, as well as psychosocial obstacles in the form of external pressure from people closest to them regarding hereditary problems and internal pressure in the form of anxiety.